Comparative Analysis of Solar Radiation Forecasting Techniques in Zacatecas, Mexico - Martha Isabel Escalona-Llaguno; Luis Octavio Solís-Sánchez; Celina L. Castañeda-Miranda; Carlos A. Olvera-Olvera; Ma. del Rosario Martinez-Blanco; Héctor A. Guerrero-Osuna; Rodrigo Castañeda-Miranda; Germán Díaz-Flórez; Gerardo Ornelas-Vargas (Applied Sciences, 2024)
This work explores the prediction of daily Global Horizontal Irradiance (GHI) patterns in the region of Zacatecas, Mexico, using a diverse range of predictive models, encompassing traditional regressors and advanced neural networks like Evolutionary Neural Architecture Search (ENAS), Convolutional Neural Networks (CNN), Recurrent Neural Networks (RNN), and Meta’s Prophet. This work addressing a notable gap in regional research, and aims to democratize access to accurate solar radiation forecasting methodologies. The evaluations carried out using the time series data obtained by Comisión Nacional del Agua (Conagua) covering the period from 2015 to 2018 reveal different performances of the model in different sky conditions, showcasing strengths in forecasting clear and partially cloudy days while encountering challenges with cloudy conditions. Overall, correlation coefficients (r) ranged between 0.55 and 0.72, with Root Mean Square Error % (RMSE %) values spanning from 20.05% to 20.54%, indicating moderate to good predictive accuracy. This study underscores the need for longer datasets to bolster future predictive capabilities. By democratizing access to these predictive tools, this research facilitates informed decision-making in renewable energy planning and sustainable development strategies tailored to the unique environmental dynamics of the region of Zacatecas and comparable regions.